2015
DOI: 10.1093/nar/gkv721
|View full text |Cite
|
Sign up to set email alerts
|

ZNF555 protein binds to transcriptional activator site of 4qA allele andANT1: potential implication in Facioscapulohumeral dystrophy

Abstract: Facioscapulohumeral dystrophy (FSHD) is an epi/genetic satellite disease associated with at least two satellite sequences in 4q35: (i) D4Z4 macrosatellite and (ii) β-satellite repeats (BSR), a prevalent part of the 4qA allele. Most of the recent FSHD studies have been focused on a DUX4 transcript inside D4Z4 and its tandem contraction in FSHD patients. However, the D4Z4-contraction alone is not pathological, which would also require the 4qA allele. Since little is known about BSR, we investigated the 4qA BSR f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…It is known that there is a striking link between ANT1 and mitochondrial uncoupling in skeletal muscle, which refers to the dissociation of mitochondrial respiratory chain activity from ATP synthesis in OXPHOS, due to a proton leakage across the inner mitochondrial membrane33. It has been demonstrated that ANT1 is overexpressed in muscle of facioscapulohumeral muscular dystrophy (FSHD) patients34. FSHD is characterized by the adult onset of progressive weakness in muscles of the face, shoulders, feet and hips.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that there is a striking link between ANT1 and mitochondrial uncoupling in skeletal muscle, which refers to the dissociation of mitochondrial respiratory chain activity from ATP synthesis in OXPHOS, due to a proton leakage across the inner mitochondrial membrane33. It has been demonstrated that ANT1 is overexpressed in muscle of facioscapulohumeral muscular dystrophy (FSHD) patients34. FSHD is characterized by the adult onset of progressive weakness in muscles of the face, shoulders, feet and hips.…”
Section: Discussionmentioning
confidence: 99%
“…Analogously to DUX4 , the ANT1 locus is located at 4q35 and has been shown to be upregulated in FSHD [ 126 , 127 ], especially in the early stages of the disease [ 128 ], although with contrasting results [ 51 , 129 , 130 ]. Molecularly, zinc-finger protein 555 (ZNF555) binding to a D4Z4 4qA located enhancer was shown to play a critical role in regulating ANT1 promoter activity, particularly in FSHD [ 131 ]. Intriguingly, transgenic mice with a two-fold increased ANT1 expression progressively develop muscle wasting [ 132 ], suggesting that aberrant ANT1 expression could contribute to FSHD variable penetrance.…”
Section: The Role Of Mitochondria In Fshdmentioning
confidence: 99%
“…Our observation that a 2-fold increase of ANT1 is sufficient to cause severe muscle atrophy could have direct implications for human diseases such as FSHD and dilated cardiomyopathy that are associated with Ant1 activation ( Dorner et al., 1997 ; Gabellini et al., 2002 ; Kim et al., 2015 ; Laoudj-Chenivesse et al., 2005 ). FSHD is primarily linked to the ectopic expression of Dux4 in the skeletal muscle.…”
Section: Discussionmentioning
confidence: 81%